Pretreatment of Sludge Palm Oil (SPO) for biodiesel production by esterification - Hayyan, Adeeb; Alam, Md. Zahangir; Kabbashi, Nassereldeen Ahmed; Mirghani, Mohamed Elwathig Saeed (2008)
Sludge palm oil is a significant raw martial with above than 40% FFA for biodiesel production. The problem with processing these low cost oils is that they often contain large amounts of free fatty acids that cannot be converted to biodiesel using an alkaline catalyst. In this study, a comparison of acids catalyzed potential is described to reduce the free fatty acids content of these feed stocks. An acid-catalyzed was using in pretreatment of sludge palm oil with present alcohol to esterify the free fatty acids before trasestifying the triglycerides with an alkaline catalyst to complete the reaction. The process was performed with sludge palm oil containing 48% FFA. The types of an acids-catalyzed were two strong acid and weak acid (H2SO4, HCl and CH3COOH) wt/wt respectively. The reaction mixture was allowed to settle in order to calculate the yield of product in different ratio. Conditions of the process are followed a molar ratio methanol/oil 10:1 with stirrer speed of 400 rpm for 1 hr reaction time at 60 C. The study showed that acid level of the high free fatty acids feed stocks could be reduced from 48%FFA to less than 2% FFA using sulfuric acid and less than 7% FFA by using hydrochloric acid with large amount of water. But it is obvious that addition of acetic acid increased the free fatty acids. The samples after reducing the FFA below than 2%FFA the transesterification reaction were completed with an alkaline catalyst to produce biodiesel.